Towards a Comprehensive, Integrated, and Effective Social Assistance System in Indonesia - World Bank Group (World Bank, Jakarta, 2017)
Since 2010, the Government of Indonesia (GoI) has set official poverty reduction targets and emphasized the importance of a well-functioning social assistance system in continued poverty reduction. However, despite the efforts in expanding coverage of the social protection system, the pace of poverty reduction in Indonesia has slowed significantly in recent years, while both chronic poverty and vulnerability have persisted. Moreover, income inequality is on the rise, while access to opportunities remain unequal. This report reassesses the strengths and weaknesses of Indonesia’s main social assistance programs, and proposes feasible reform options, both program-by-program and for the social assistance system as a whole. This 2017 updated report seeks to provide evidence of the progress made between 2011 and 2017, together with relevant benchmarks for future reforms and policy planning. The review presents analytical evidence on salient program features and issues, and proposes additional efforts and options toward a truly integrated system.